Intensive BP control in patients with CKD and risk for adverse outcomes - Ku, Elaine; McCulloch, Charles E.; Inker, Lesley A.; Tighiouart, Hocine; Schaefer, Franz; Wühl, Elke; Ruggenenti, Piero; Remuzzi, Giuseppe; Grimes, Barbara A.; Sarnak, Mark J. (Journal of the American Society of Nephrology, 2023)
The effect of intensive BP lowering (to systolic BP of ,120 mm Hg) on the risk of kidney failure requiring KRT remains unclear in patients with advanced CKD. Such patients were not well represented in trials evaluating intensive BP control.
Online veröffentlicht am 17. Januar 2023
Gesehen am 07.12.2023